Kerjasama Indonesia dengan North Atlantic Treaty Organization dalam Global Army Trade Tahun 2019-2024 - Maulana Fasha Aralea; Achdijat Sulaeman (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Indonesia is the most powerful country in Southeast Asia and the 13th in the world, according to research from Global Firepower and the Stockholm International Peace Research Institute (SIPRI). However, Indonesia requires cooperation with other countries in military diplomacy on the international stage, while upholding the principle of an independent and active foreign policy. Therefore, Indonesia can collaborate with the North Atlantic Treaty Organization in global arms sales, including joint exercises. This research method uses qualitative research, which utilizes conditional observations on natural objects and data collection as explanatory information. The study results indicate that Indonesia can collaborate with North Atlantic Treaty Organization member states in defense development, such as the physical construction of the Minimum Essential Force (MEF) and Indonesia's role in joint exercises, with the caveat that Indonesia does not have an official relationship with NATO as a non-member country.